Relationship of Ki-67 index in biopsies of metastatic breast cancer tissue and circulating tumor cells (CTCs) at the time of biopsy collection - Deutsch, Thomas M.; Fischer, Chiara; Riedel, Fabian; Haßdenteufel, Kathrin; Michel, Laura L.; Sütterlin, Marc; Riethdorf, Sabine; Pantel, Klaus; Wallwiener, Markus; Schneeweiss, Andreas; Stefanovic, Stefan (Archives of gynecology and obstetrics, 2024)
The proliferation marker Ki-67 is a major pathological feature for the description of the state of disease in breast cancer. It helps to define the molecular subtype and to stratify between therapy regimens in early breast cancer and helps to assess the therapy response. Circulating tumor cells (CTCs) are a negative prognostic biomarker for progression free (PFS) and overall survival (OS) in patients with metastatic breast cancer. Therefore, the CTC count is often described as surrogate for the tumor burden. Both, decrease of Ki-67 and CTC count are considered as evidence for therapy response. The presented work analyzed the correlation between the Ki-67 indices of metastatic tissue biopsies and CTC counts in biopsy time-adjacent peripheral blood samples.